PENINGKATAN PEMAHAMAN AGAMA BAGI GENERASI MUDA MELALUI PENGUATAN PENDIDIKAN KELUARGA DI NAMU UKUR SELATAN KABUPATEN LANGKAT - Tambunan, Nurhalima (Jurnal Ilmiah Al-Hadi, 2019)
This service was carried out in the South Namu Ukur Village, Sei Bingai District, Langkat Regency. This activity aims to instill an image for the younger generation to seek to increase religious understanding for family members through informal education through strengthening education in families. The specific target inthis service is to provide an understanding of the importance of education as a stronghold in responding to other forms of education. Through a coaching program that can later be carried out on an ongoing basis, it can create a resilient young generation. Youth are the next generation that physically and thought can easily accept change. The expected outcome of this dedication is that it can be published in scientific journals thathave ISSN and be additional information in the making of teaching materials in communication science courses, especially organizational communication and group communication. This dedication will be carried out in the southern Namu measuring village consisting of 10 environments including the Namu Measuring Environment, Simpang Tiga Environment, Tanjung Karo Environment, Modeling Environment, Sidodadi Environment, Siriang-jovial Environment, Suka Rame Environment, Sido Rukun Environment, Lau Workshop environment , South Namu Measuring Environment. The length of service is 2 months, the approach used is a case study by gathering various kinds of information which is then processed to get a solution so that the problems revealed can be solved.